Ultra-fast silicon detectors : design, tests, and performances /: design, tests, and performances. (2021) - Ferrero, Marco; Arcidiacono, Roberta; Mandurrino, Marco; Sola, Valentina; Cartiglia, Nicolò
No abstract available